Bodies of Stone in the Media, Visual Culture and the Arts - Conte, Pietro; Grespi, Barbara; Pinotti, Andrea; Violi, Alessandra 1963- (Amsterdam University Press, 2020)
If mediatization has surprisingly revealed the secret life of inert matter and the 'face of things', the flipside of this has been the petrification of living organisms, an invasion of stone bodies in a state of suspended animation. Within a contemporary imaginary pervaded by new forms of animism, the paradigm of death looms large in many areas of artistic experimentation, pushing the modern body towards mineral modes of being which revive ancient myths of flesh-made-stone and the issue of the monument. Scholars in media, visual culture and the arts propose studies of bodies of stone, from actors simulating statues to the transmutation of the filmic body into a fossil; from the real treatment of the cadaver as a mineral living object to the rediscovery of materials such as wax; from the quest for a "thermal" equivalence between stone and flesh to the transformation of the biomedical body into a living monument
Description based on online resource; title from PDF title page (publisher's Web site, viewed 26. Aug 2020)
Keywords: Communication; Film; Media; ART / Subjects & Themes / Human Figure; Statues in art